DOC2B is a negative regulator of Wnt/β-catenin signaling pathway in cervical cancer. (June 2022) - Adiga, Divya; Bhat, Samatha; Chakrabarty, Sanjiban; Kabekkodu, Shama Prasada
Abstract: DOC2B is a ubiquitously expressed isoform of the double C-2 protein family that requires Ca 2+ for most of its physiological functions. Initial findings have indicated that DOC2B participates in exocytosis, vesicular transport, insulin secretion and regulation, glucose homeostasis, and neurotransmitter release. Aberrant expression of DOC2B has been reported in diabetes, leukemia, and cervical cancer (CC). Our earlier studies have demonstrated the inhibitory effects of DOC2B on CC cell proliferation, migration, invasion, and EMT and suggested the possible role of DOC2B in Wnt signaling inhibition. However, the association between DOC2B downregulation and Wnt/β-catenin signaling activation and the underlying molecular mechanism remain elusive. Herein, we found that DOC2B inhibited Wnt/β-catenin pathway by enhancing the expression of the components of the CTNNB1 destruction complex and by fostering proteasomal degradation of CTNNB1. The translocation of CTNNB1 to the nucleus and its interaction with TCF/LEF family transcription factors was perturbed in the presence of DOC2B in a GSK3β independent manner. Further, we have identified DKK1 as one of the upregulated genes in the presence of DOC2B. DKK1 inhibition in DOC2B expressing cells by WAY262611 reactivated Wnt/β-catenin signaling, relieved DOC2B induced senescence, and alleviated the inhibitory effects of DOC2B on the aforementioned malignant behaviors. We have provided evidence for DOC2B-DKK1-senescence-Wnt/β-catenin-EMT signaling crosstalk to have tumor growth regulatory functions in CC. Thus, targeting DOC2B-DKK1-senescence-Wnt/β-catenin-EMT signaling crosstalk via activation of DOC2B may offer a novel approach to restraint malignant behaviors in CC. Graphical Abstract: ga1